2016
DOI: 10.1016/j.mseb.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

High thermoelectric performance of fullerene doped Bi0.5Sb1.5Te3 alloys

Abstract: In this paper, we report our recent experimental findings on the enhancement of thermoelectric performance of C 60 doped Bi 0.5 Sb 1.5 Te 3 bulk alloys. Incorporation of a small amount of C 60 significantly reduces the crystalline particle size and leads to closely packed nanostructure, whilst slightly improve the electric conductivity in the measured temperature range. In addition, a minimum thermal conductivity of 0.4 W/(mK) at 358 K was observed, which is identified to be caused by the strong lattice phonon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…For undoped sample S1, compared with those synthesized by mechanical alloying 19 and spark plasma sintering (SPS), 39 its nanostructuring obtained by hydrothermal synthesis lowers the thermal conductivity by about 31-50% at room temperature, due to the contribution of additional phonon scattering, implying that our hydrothermal synthesis method is effective on reducing the thermal conductivity. As for sample S2, its average thermal conductivity in the temperature range of 150-350 C is about 0.71 W m À1 K À1 , approximately 12%, 21%…”
Section: Methodsmentioning
confidence: 95%
“…For undoped sample S1, compared with those synthesized by mechanical alloying 19 and spark plasma sintering (SPS), 39 its nanostructuring obtained by hydrothermal synthesis lowers the thermal conductivity by about 31-50% at room temperature, due to the contribution of additional phonon scattering, implying that our hydrothermal synthesis method is effective on reducing the thermal conductivity. As for sample S2, its average thermal conductivity in the temperature range of 150-350 C is about 0.71 W m À1 K À1 , approximately 12%, 21%…”
Section: Methodsmentioning
confidence: 95%
“…On the other hand, because the charge carrier wavelengths are larger than the size of a fullerene molecule, scattering of electrons or holes is comparatively negligible. 356 The effect of C60 in Bi2-xSbxTe3 alloys has also been extensively studied, [357][358][359][360][361][362] with results showing that fullerene molecules act as phonon blocking sites, reducing L, and enhancing the TE performance. In addition, C60 also can efficiently reduce the L of other TE systems including skutterudites 363,364 and Cu-/Agbased chalcogenides.…”
Section: Articlementioning
confidence: 99%
“…Up to now, many different techniques have been applied to enhance the zT values of Bi 2 Te 3 -based alloys, including doping/alloying, defect engineering, , nanostructuring, or texturing. Previous studies revealed that the peak zT values of Bi 2 Te 3 -based materials outreach 1.2 around 300 K for alloyed compositions and after applying complex synthesis procedures. Commercial materials are usually synthesized in the form of single crystals or zone-melted ingots with a high degree of texture. ,, However, the high deformation texturing techniques applied during the synthesis lead to high production cost and poor mechanical stability of the materials. ,,, …”
Section: Introductionmentioning
confidence: 99%